ImageMagick tricks : web image effects from the command line and PHP : unleash the power of ImageMagick with this fast, friendly tutorial and tips guide /: web image effects from the command line and PHP : unleash the power of ImageMagick with this fast, friendly tutorial and tips guide. (2006) - Unknown
No abstract available